Ethical Attitude of the Evangelical Christian Church in Halmahera (GMIH) Towards the 2024 Political Year in North Halmahera - F. Dalensang, Ramelia (IAKN TORAJA, 2024)
Abstract: The purpose of this study is to find out the ethical attitude of the Church to prevent the impact of election differences in political moments and to be involved in practical politics. This study employs a qualitative methodology utilizing a descriptive-analytic approach. According to the study's findings, the process of familiarizing the congregation with politics has been ongoing for a considerable period in the Evangelical Christian Church in Halmahera (GMIH) in North Maluku. However, the issue is that this socialization effort has yet to be successfully implemented among all congregation members. Another research finding about the Church's engagement in practical politics is that GMIH abstains from engaging in practical politics. The Church aims to foster a comprehensive comprehension of politics. It encourages all congregation members to exercise their rights to vote and run for office in the upcoming 2024 regional elections. Keywords: Church, Ethical Attitude, Politic. Abstrak: Tujuan dalam penelitian ini adalah untuk mengetahui sikap etis Gereja untuk mencegah dampak perbedaan pemilihan dalam momen politik dan dapat terlibat dalam politik praktis. Kajian ini menggunakan metode kualitatif dengan pendekatan deskriptif analisis. Berdasakan hasil penelitian, proses sosialiasi kepada jemat untuk memberikan pemahaman yang baik kepada jemat tentang politik, telah di lakukan sejak lama kepada jemaat, namun yang menjadi permasalahan adalah bahwa kegiatan sosialisasi ini belum dapat di laksanakan ke seluruh jemaat Gereja Masehi Injili di Halmahera (GMIH) yang ada di Maluku Utara. Hasil penelitian yang lain terkait keterlibatan Gereja dengan politik praktis adalah GMIH tidak terlibat dalam politik praktis. Gereja hadir untuk memberikan untuk memberikan pemahaman politik yang baik, dan mengajak seluruh jemat untuk memberikan haknya baik untuk memilih dan dipilih pada pemilu maupun pemilukada tahun 2024. Kata Kunci: Gereja, sikap etis, politik.